Entropy-based quantification of a product’s BOM blocking effect - César Martínez-Olvera; Yasser Davizón-Castillo; Jaime Mora-Vargas (Production and Manufacturing Research: An Open Access Journal, 2016)
Manufacturing complexity increases as a result of product configuration, and even though different manufacturing complexity measures have been developed, none of them seem to put attention to the blocking effect a product’s bill-of-material imposes to the process flow. The following paper extends the research presented by the authors in a previous paper, where a set of entropic formulations were developed to act as an increase/decrease indicator of a manufacturing system’s performance parameters. Our findings show that the improvements to the entropic formulations provide results that are closer to the system’s performance parameters final values.